2017
DOI: 10.1111/nin.12216
|View full text |Cite
|
Sign up to set email alerts
|

Nursing assistants matters—An ethnographic study of knowledge sharing in interprofessional practice

Abstract: Interprofessional collaboration involves some kind of knowledge sharing, which is essential and will be important in the future in regard to the opportunities and challenges in practices for delivering safe and effective health care. Nursing assistants are seldom mentioned as a group of health care workers that contribute to interprofessional collaboration in health care practice. The aim of this ethnographic study was to explore how the nursing assistants' knowledge can be shared in a team on a spinal cord in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…A previous study on interprofessionalhjn collaboration that included NAs reported that some nurses perceived NAs as supportive of them as well as their patients (Lancaster et al, 2015). Another qualitative study found that NAs tended not to participate in formal multidisciplinary meetings (Lindh Falk et al, 2017), suggesting that patient information shared by nurses and other staff members may not be shared with NAs. As nurses have the closest working relationships with NAs, it is important for nurses to express information to them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study on interprofessionalhjn collaboration that included NAs reported that some nurses perceived NAs as supportive of them as well as their patients (Lancaster et al, 2015). Another qualitative study found that NAs tended not to participate in formal multidisciplinary meetings (Lindh Falk et al, 2017), suggesting that patient information shared by nurses and other staff members may not be shared with NAs. As nurses have the closest working relationships with NAs, it is important for nurses to express information to them.…”
Section: Discussionmentioning
confidence: 99%
“…Nakaoka, Mitani, Tomizawa, and Shibutani (2016) found that inadequate information‐sharing between nurses and NAs could lead to ineffective patient care. Nurses can access information about patients' diseases, care requirements, and medical decisions, whereas NAs can access valuable patient information through providing regular care (Kunimatsu, 2015; Potter & Grant, 2004), which can also be used to support nurses' work (Lindh Falk, Hult, Hammar, Hopwood, & Abrandt, 2017). As frontline care providers, NAs develop close relationships with patients, and often have information on contextual matters, such as patients' home lives and their feelings regarding hospitalization, which may differ from information obtained by nurses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholders and policy‐makers might need to consider the effective strategies of encouraging nurses and highlighting the value of implementing stroke‐rehabilitation care (Kitson, ). Moreover, nursing practice has cultural characteristics, varying in different contexts (Lindh Falk, Hult, Hammar, Hopwood, & Abrandt Dahlgren, ; Tsujimura et al, ). Consideration of these facilitators in the specific cultural context might be necessary to develop effective strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The labeling concept suggests those with power are able to construct a reality that has the potential to disadvantage those with less power. It could be proposed that the assistant dialogue has such power, potentially hidden ( 40 ), with limited interprofessional inclusion ( 41 ) which in turn may impact upon patient safety ( 42 ). Earlier work has however described the RNs’ awareness of these labels and the effort required to manage them so as not to subject the patient to inequity of care and treatment ( 43 ).…”
Section: Discussionmentioning
confidence: 99%